Ideas de los alumnos sobre digestión : aspectos anatómicos - Banet Hernández, Enrique; Núñez, Francisco (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this article we analize the ideas that students from different levels (FOB, BUP, Teachers' Training college) as well as some teachers have in relation to some specific anatomical aspects of the digestive system. The results obtained show a very low effect of instruction on the conceptual progression of the student, and they suggest, as a working hypothesis, specific classroom tasks which could favour a more useful and lasting learning of the above mentioned concepts.